Blues as Cultural Resistance: Representing Black Struggle through Music in Sinners 2025 - Ramadhanti, Rahma; Sujiwa, Krisna (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the role of blues music in Sinners, directed by Ryan Coogler, as a form of cultural resistance against racial oppression during the Jim Crow era. It adopts Tricia Rose’s theory of Cultural Resistance and applies a qualitative interpretive method within the broader framework of Cultural Studies. The analysis focuses on how blues operates beyond its function as background music and instead serves as a narrative and ideological device that shapes meaning and representation. The findings identify three interrelated dimensions. First, blues functions as a medium of political expression that articulates the lived experiences and collective memory of Black communities. Second, the film presents a clear politics of sound and space, particularly in locations such as juke joints, where music becomes a site of negotiation, control, and resistance. These spaces are not neutral; they structure who can speak, perform, and be heard. Third, the narrative highlights an ongoing struggle to reclaim identity and cultural ownership in the face of appropriation and commodification. Blues emerges as both a cultural resource and a contested terrain shaped by unequal power relations. Overall, the study demonstrates that blues in Sinners operates as a hidden transcript, a form of symbolic protection, and a site of cultural contestation. These roles reveal both the resilience and the vulnerability of Black expressive culture under systemic oppression. This research contributes to film studies, sound studies, and cultural studies by emphasizing how material and spatial conditions influence practices of resistance and cultural production.